Management And Outcome Of Diabetic Charcot’s Foot: Jabir Abueliz Diabetic Center Experience 2019 (JADC) - Mohamed, Shazali Mohamed Ahmed; Widatalla, Abu Bakr Hassan (مجلة الجزيرة للعلوم الصحية; مجلد 16 عدد 1 (2020), 2020)
Charcot foot is a rare but a serious diabetic related condition. Usually it is misdiagnosed although its prognosis related to timely and proper management. Objective: To study the management and outcome of diabetic Charcot’s foot in Jabir AbuEliz diabetic center in period between 2012 and 2019. Methods: A combined retro-prospective descriptive analytical study and hospital based. Study conducted to 134 diabetic patients with charcot joint attended to JADC during the study period. The study sample was calculated by total coverage. Study questionnaires captured mainly quantitative data. Data analyzed by using SPSS version 21. Results: 134 diabetic patients with charcot joint were involved in this study, most of the patients were males, in the age group 51-60 years and had NIDDM associated with other medical disorders.  At the time of presentation, 91% of the patients presented with swelling and 53.7% of the patients had pain. On examination of the foot; 84.3% of the patients had swelling and 59.7% of the patients had dry skin. Hammer toes deformity was the commonest feet deformity. Based on modified Sella and Barrette classification, 17.2% of the patients in grade 1. Casting was performed to all patients with good outcome to 91.1% of the patients. Conclusion: This study reveals that grade 0,1&2 Charcot neuroarthropathy feet had good outcome if properly recognized and early managed. The total contact cast (TCC) and CAM walker is effective in the management.